2020
DOI: 10.1371/journal.pone.0237658
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and comparing data mining algorithms for prediction of recurrence of breast cancer

Abstract: Breast cancer is the most common invasive cancer and the second leading cause of cancer death in women. and regrettably, this rate is increasing every year. One of the aspects of all cancers, including breast cancer, is the recurrence of the disease, which causes painful consequences to the patients. Moreover, the practical application of data mining in the field of breast cancer can help to provide some necessary information and knowledge required by physicians for accurate prediction of breast cancer recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
1
18
2
Order By: Relevance
“…HER2 positivity rate, tumor size, and age were not independent risk factors for local recurrence and metastasis in this study. However, other studies have found that HER2 status, tumor size, and age are risk factors for recurrence [24,25]. This inconsistency is likely due to a small sample size and short follow-up period in our report.…”
Section: Discussioncontrasting
confidence: 69%
“…HER2 positivity rate, tumor size, and age were not independent risk factors for local recurrence and metastasis in this study. However, other studies have found that HER2 status, tumor size, and age are risk factors for recurrence [24,25]. This inconsistency is likely due to a small sample size and short follow-up period in our report.…”
Section: Discussioncontrasting
confidence: 69%
“…Their results inspired the models developed in the current study, which integrate gene expression profiling data and artificial intelligence algorithms in improved diagnostic tools for CRC. In another recent study, accuracy in predicting breast cancer recurrence was compared among conventional and recently developed data mining algorithms [ 4 ]. According to the comparison results, the decision tree C5.0 algorithm may be the best tool for predicting breast cancer recurrence, particularly 3-year recurrence, in patients who are in distant recurrence stage or nonrecurrence stage.…”
Section: Introductionmentioning
confidence: 99%
“…M.A.Fahami et al [12] clustered the colon cancer patients into 2 important categories and as a result they found out top 20 genes that are effective in both the categories. Alireza et al [13] applied novel and traditional data mining methods viz, linear vector quantization (LVQ) neural network (NN), multi-layer perceptron (MLP), Bayesian NN, Decision Tree (DT-C5.0), kernel principal component analysis with support vector machine (KPCA-SVM), and random forest (RF). The author clearly demonstrates the impact of machine learning technology on breast cancer recur classification.…”
Section: Related Research Workmentioning
confidence: 99%
“…It was found that all the three algorithms were performing well but kNN outperforms the other two by a difference of around 0.4 percent in accuracy. ROC [11], [14], [15], [18] 4 AUC [11], [13], [15], [18] 4 F-Measure [13], [14], [18], [19] 4…”
Section: Related Research Workmentioning
confidence: 99%